(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the role of Iodine Polymers (Idomarine) in the treatment of Oligomenorrhea and Polycystic ovarian disease in Students for Sir Syed Medical College for girls Karachi. Study Design: Interventional study. Place and Duration: Outpatient department of Sir Syed Hospital from 1st November 2013 to 30 April 2014. Methodology: One hundred students were included in the study, after taking an informed consent. Information was gathered and rest assured that they were not taking any medication within last 6 months. The Investigations carried out included serum fasting insulin levels, thyroid profile, serum F.S.H L.H and prolactin and ultrasound of pelvis. Capsule iodine polymer (Idomarine) 50mg twice daily were prescribed for eight weeks to all the students. The information about study variables were collected by administrating a predesigned questioner. Results: A total of 100 students were included in this study. Iodine polymer (Idomarine) 50mg twice daily for 8 weeks was given to them. Most of the students around 56% able to perform serum FSH & LH. Ultrasound was done by 30% of the students and almost all showed polycystic ovaries. Thyroid profile was done in 11% & serum insulin was carried out in only 3 % of students. Almost all of them had some symptoms majority complained of menstrual irregularity 42%, followed by weight gain in 26% pelvic pain 21% & hirsutism 11%. The side effect of the drug was minimal, and majority 81% had no symptoms. Mood swings were noted in 11% of the students followed by nausea 6% and headaches in 2%. Majority responded to the medication only 2 did not respond to it and were put on alternate drugs. Conclusion: Polycystic ovarian disease is on the rise in young girls of reproductive age group. It can be predicted reliably with the help of clinical laboratory investigations and ultrasound. Iodine polymer was used by all students and showed marked improvement in symptoms of Polycystic ovarian disease syndrome. The iodine Polymer complex (Idomarine) used in the treatment of PCO and menstrual irregularity helped almost all the students without the intervention of any other hormonal medication not to forget they were also told to have life style modification, along with dietary restrictions.